The big chill: quantifying the effect of the 2014 North American cold wave on hemlock woolly adelgid populations in the central Appalachian Mountains. Issue 3 (18th July 2017) - Tobin, Patrick C.; Turcotte, Richard M.; Blackburn, Laura M.; Juracko, John A.; Simpson, Brian T.
Abstract: The ability to survive winter temperatures is a key determinant of insect distributional ranges and population dynamics in temperate ecosystems. Although many insects overwinter in a state of diapause, the hemlock woolly adelgid [ Adelges tsugae (Annand)] is an exception and instead develops during winter. We studied a low density population of A. tsugae, which undergoes two generations per year, in a forested area in which its only available host plant, eastern hemlock ( Tsuga canadensis ), was patchy and scarce. In January 2014, this area also experienced an exceptionally cold winter due to a southward shift in the North Polar Vortex. We used 3 years of systematic sampling prior to the 2014 cold wave, and 1 year following, to quantify the effect of the 2014 cold wave on A. tsugae population dynamics. We observed a strong negative correlation between the number of days below sub‐zero temperature thresholds and A. tsugae, and estimated that the 2014 cold wave resulted in at least a 238% decrease in its population growth rate. However, we also observed that the detrimental effect of the 2014 cold wave to A. tsugae was short‐lived, as populations measured in the late summer of 2014 rebounded to pre‐2014 cold wave densities. This study highlights the effect that cold winter weather events can have on a winter active insect species, and the speed at which populations can recover from stochastic mortality events.